2017
DOI: 10.1002/maco.201709684
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Ti35Zr28Nb in Hanks’ solution and 3.5 wt% NaCl solution

Abstract: This research assessed the corrosion behaviour of Ti35Zr28Nb compared to that of commercial purity Ti (CP Ti) Grade 2 under crevice‐corrosion conditions in: (i) Hanks’ solution at 37 °C and (ii) 3.5 wt% NaCl solution at 95 °C. Both Ti35Zr28Nb and CP Ti showed low corrosion rates. There was no evidence of crevice corrosion indicating that both CP Ti and the Ti alloy were not sensitive to crevice corrosion under the conditions studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The Ti intermediate layer enhances the reaction (Equation ) compared with the single layer TiN coating but the exact mechanism requires further study. The potential of TiAl 6 V 4 substrate increases initially and then decreases revealing that formation and dissolution of the native oxide layer (mainly TiO 2 ) reaches equilibrium after approximately 60 s. The results suggest that surface oxide layer is initially dissolved by aggressive ions before equilibrium and dissolution of the oxide layer proceeds as follows: normalH2normalO+TinormalO2+normalH+Ti(OH)3+…”
Section: Resultsmentioning
confidence: 89%
“…The Ti intermediate layer enhances the reaction (Equation ) compared with the single layer TiN coating but the exact mechanism requires further study. The potential of TiAl 6 V 4 substrate increases initially and then decreases revealing that formation and dissolution of the native oxide layer (mainly TiO 2 ) reaches equilibrium after approximately 60 s. The results suggest that surface oxide layer is initially dissolved by aggressive ions before equilibrium and dissolution of the oxide layer proceeds as follows: normalH2normalO+TinormalO2+normalH+Ti(OH)3+…”
Section: Resultsmentioning
confidence: 89%
“…Figure a provides a schematic of the crevice‐corrosion assembly . Figure b provides a photo of an actual crevice corrosion assembly, in this case containing three specimens each of the porous CP–Ti samples, and the porous Ti35Zr28Nb samples.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Ti35Zr28Nb is a relatively newly developed Ti alloy processing a good combination of properties and is well suited for medical implant applications, based on extensive research on beta‐Ti alloys . Prior work found that Ti35Cr28Nb had high corrosion resistance, and was highly resistant to crevice corrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabricated alloy also exhibits excellent mechanical properties of trabecular bone with the elastic modulus (0.2-5) GPa and compressive strength (4-70) MPa. Whereas [17][18][19] performed an experimental investigation on the corrosion behavior of Ti35Zr28Nb in Hanks' solution at 37 °C and 3.5 wt% NaCl solution at 95 °C. These investigations indicate that there was no evidence of crevice corrosion under various conditions.…”
Section: Selective Laser Sintering Of β-Ti35zr28nbmentioning
confidence: 99%